Assessing Differential Item Functioning on the Test of Relational Reasoning - Dumas, Denis; Alexander, Patricia (Frontiers in Education, 2018)
The Test of Relational Reasoning (TORR) is designed to assess the ability to identify complex patterns within visuospatial stimuli. The TORR is designed for use in school and university settings, and therefore, its measurement invariance across diverse groups is critical. In this investigation, a large sample, representative of a major U.S. university on key demographic variables, was collected, and the resulting data were analyzed using a multi-group, multidimensional item-response theory model-comparison procedure. No significant differential item functioning (DIF) was found on any of the TORR items across any of the demographic groups of interest. This finding is interpreted as evidence of the cultural fairness of the TORR, and potential test-development choices that may have contributed to that cultural fairness are discussed.